Teacher–Student Interaction Quality and Academic Motivation in Neurodivergent Learners: The Mediating Role of Social Relatedness - Pelc, Vladimir; Erves, Marit; Ternar, Aleksander (Psychological Research in Individuals with Exceptional Needs, 2025)
This study aimed to investigate the effect of teacher–student interaction quality on academic motivation in neurodivergent learners, with social relatedness examined as a mediating variable. A descriptive correlational design was employed using a sample of 403 neurodivergent secondary school students in Slovenia, selected based on Krejcie and Morgan’s sampling table. Standardized instruments were used to assess teacher–student interaction quality, social relatedness, and academic motivation, all measured on 7-point Likert scales. Data were analyzed using Pearson correlation in SPSS-27 to explore bivariate associations and Structural Equation Modeling (SEM) in AMOS-21 to test the hypothesized mediating model. Model fit was evaluated using multiple indices, including χ²/df, GFI, AGFI, CFI, TLI, and RMSEA. The results indicated significant positive correlations among all variables: teacher–student interaction quality was positively correlated with social relatedness (r = .61, p < .001) and academic motivation (r = .55, p < .001), while social relatedness was strongly correlated with academic motivation (r = .67, p < .001). The SEM analysis showed an acceptable model fit (χ²/df = 2.35, CFI = 0.97, RMSEA = 0.057). Teacher–student interaction quality had significant direct effects on both social relatedness (β = .61, p < .001) and academic motivation (β = .26, p < .001). Social relatedness significantly predicted academic motivation (β = .58, p < .001), and also mediated the relationship between teacher–student interaction and academic motivation (indirect β = .35, p < .001), confirming a partial mediation model. The findings underscore the critical role of social relatedness in explaining how supportive teacher–student interactions enhance academic motivation among neurodivergent learners. Educational interventions that strengthen relational dynamics in inclusive classrooms may foster higher motivation and academic engagement in this population.